ANALISIS KONSEP TA’WIL IBN ‘ARABI TERHADAP AYAT AL-QUR’AN - Wahyudi Wahyudi (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
This article tries to enlighten and analyze the concept of ta'wil of Ibn 'Arabi on the verses of the Holy Qur-an. In order to understand the Holy Qur-an, Sufis used a method the-so-called Ta'wil.Ta'wil Sufis for in the name of the Holy Qur-ann is based on the belief that the Qur-an contains two sides, zahir (is the world of bodies whereas batin is the world of souls) and inner/inward/hidden. This dichotomy also becomes the basis for ta'wil of Ibn ‘Arabi on the verses of the Holy Qur-an. He called it the term Al-‘Ibarah and Al-Isharah, essentially this term has similarities with zahir and batin. The semantic domain of the Qur-an iszahir Al-Ibarahkalam Allah (S.W.T.). In Ibn ‘Arabi's perspective there are two kinds of kalam, first when which does not need the medium used to express the language either in the form of pronunciation or numbers. Secondly, kalam are bond by substance or medium to express language, whether it is in the form of pronunciation or numbers. From the two types of Kalam, according to Ibn ‘Arabi only essential messages can produce knowledge, while kalam which is bond by substance only produce understandings.Al-Fahm is just an illustration of many images of knowledge, it is not knowledge.